PENGARUH KUALITAS SDM DAN MENTORING TERHADAP KINERJA DENGAN PEMBERDAYAAN PEREMPUAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PEREMPUAN PELAKU UMKM DESA BATU MERAH) - Hestianty F Manuhutu (Soso-Q : Jurnal Manajemen, 2021)
ABSTRAK The purpose of this study was to (1) analyze the influence of the quality of humanresources of women entrepreneurs in Batu Merah Village on women's empowerment (2)Analyze the influence of mentoring on empowering women entrepreneurs in Batu MerahVillage (3) Analyze the influence of women's empowerment on the performance of womenentrepreneurs in Batu Merah Village. (4) Analyzing the influence of the quality ofwomen's human resources in Batu Merah Village SMEs on their performance (5)Analyzing the influence of mentoring on the performance of women SMEs in Batu MerahVillage (6) Analyzing whether women's empowerment is able to mediate the influence ofthe quality of women's HR in Batu Merah Village on performance they (7) analyzedwhether women's empowerment was able to mediate the influence of mentoring on theperformance of women entrepreneurs in Batu Merah Village. Keywords: Quality Of Human Resources, Mentoring, Women's Empowerment, Performance, Smes, Women Entrepreneurs Of Smes.